Managing dissonant cultural heritage in regional and local development policy in the Warmińsko-Mazurskie voivodeship (Warmia-Masuria) - Poniedziałek, Jacek (Eastern European Countryside, 2025)
This article aims to analyse how cultural heritage is addressed in documents defining the objectives and directions of socio-economic development in the Warmińsko-Mazurskie voivodeship, in light of their practical implementation. This paper seeks to determine whether and how these documents and practices acknowledge that, due to the region's complex history, this heritage is characterised as dissonant. The analysis reveals that authorities often manage this awkwardness by remaining silent about much of its ethnic and religious provenance or by employing generic terms obscuring its meanings. This approach reduces the level of dissonance associated with the heritage, leading to attempts to transform it into a resource in the form of tourist attractions (sites and festivals) to contribute to the region’s development, rather than engaging in discussions about its significance or remember traumas that generate social conflicts.